Research on Backlash Nonlinearity in AC Servo-driven Precision Transmission System - Wei Zhou; Ling Zhao; Xiaolun Li; Lihong Lin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
AC servo-driven precision transmission system is mainly composed of AC servo motor, mechanical transmission parts and control parts. Because of mutual coupling between various parts, particularly transmission system in mechanical coupling vibration in non-smooth transition, it will be of great harm to safe operation of the system. This paper made some overview and built the model of AC servo-driven precision transmission system mainly from the perspective of backlash nonlinear characteristic and with simulation tool of Matlab/Simulink to analyze the influence of backlash on the precision of servo system, and then corresponding simulation curve and conclusions were shown in this paper. Do hope the work above will have certain reference significance to actual engineering application. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5394